1985
DOI: 10.1136/oem.42.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Coexposure to toluene and p-xylene in man: central nervous functions.

Abstract: ABSTRACr Sixteen men were studied in an exposure chamber to assess the effect of four hours' exposure to toluene (3.25 mmol/m3), xylene (2-84 mmol/m3), a mixture of toluene and xylene (2-20 + 0*94 mmol/m3), and a control condition. With the aid of microcomputers, subjects performed tests of simple reaction time, short term memory, and choice reaction time immediately after entering the chamber, after two, and after four hours' exposure. The results indicate that the performance on the tests was unaffected by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…Irritancy effects from xylene exposures, as a function of dose, were reported to range from turbidity and irritation of the ocular conjunctiva, to irritation of the upper airway, to severe lung congestion, to pulmonary edema and hemorrhages (Reese & Kimbrough, 1993). Increased reaction time, reduced short-term memory, and impaired postural equilibrium have been documented at xylene exposure levels ranging from 100 to 200 ppm, but not at 70 ppm (reaction time and memory reproduction only) (Olson et al, 1985). Savolainen et al (1980) reported deficits in reaction time, manual dexterity, body balance, and EEG following acute exposure to 90 ppm mxylene, while exposure to 300 ppm mixed xylene resulted in deficits on memory span, critical flicker fusion, and reaction time .…”
Section: Hydrocarbon Fuel Neurotoxicity 251mentioning
confidence: 97%
“…Irritancy effects from xylene exposures, as a function of dose, were reported to range from turbidity and irritation of the ocular conjunctiva, to irritation of the upper airway, to severe lung congestion, to pulmonary edema and hemorrhages (Reese & Kimbrough, 1993). Increased reaction time, reduced short-term memory, and impaired postural equilibrium have been documented at xylene exposure levels ranging from 100 to 200 ppm, but not at 70 ppm (reaction time and memory reproduction only) (Olson et al, 1985). Savolainen et al (1980) reported deficits in reaction time, manual dexterity, body balance, and EEG following acute exposure to 90 ppm mxylene, while exposure to 300 ppm mixed xylene resulted in deficits on memory span, critical flicker fusion, and reaction time .…”
Section: Hydrocarbon Fuel Neurotoxicity 251mentioning
confidence: 97%
“…The results of these studies indicated that the odor threshold for xylene is approximately 1 ppm (32). Brief exposure to approximately 70 ppm xylene did not affect reaction time or short-term memory (33). Inhalation exposure at 90 ppm, however, caused deleterious effects on reaction time, manual dexterity, body balance, and EEG (34).…”
Section: Xylenementioning
confidence: 99%
“…These inhibitory metabolic interactions are characterized by reduced/ delayed production and excretion of metabolites, and/or increased concentrations of parent chemical(s) in the blood and expired air. However, the health significance of several of these metabolic interactions has not been confirmed in workers occupationally exposed to binary solvent mixtures (48,49). The inhibitory metabolic interactions can be expected to result in supraadditivity with respect to the toxicity of the parent chemicals.…”
Section: Poliutantsmentioning
confidence: 99%